Automatiс Operation of a Rotary Garden Cultivator - Viktor N. Zvolinsky; Maksim A. Mosyakov (Сельскохозяйственные машины и технологии)
Abstract. The paper discusses the advantages of power-driven tillage tools as compared with machines with passive working elements, which provide for quick changing and controlling of the quality of soil crumbling, guided by the condition of the treated areas and the engine power of the power source used. (Research purpose) To develop a system for automatically maintaining the magnitude of a selected kinematic parameter during the operation of a rotary cultivator equipped with a hydraulic drive of working elements. (Materials and methods) The authors have conducted research involving patented materials on the use of automated process control systems for pre-sowing soil cultivation with tools featuring hydraulic actuators of working elements. (Results and discussion) It has been determined that the frequency comparison blocks may contain pulse shapers that are converted by the electronic control unit into a signal sent to a low-speed, high-torque adjustable motor of a Danfoss MGP-160 type. A system has been developed to automatically maintain the value of a selected kinematic parameter of a rotary cultivator by equipping its working elements with a hydraulic actuator with a two-stage hydraulic distributor controlled by an electronic unit that allows automatic adjustment of the required speed of the rotary drum cutters, optimal for the treated soil background. (Conclusions) The authors have identified a schematic diagram of an automated hydraulic drive of a rotary garden cultivator capable of tracking and adjusting the rotary drum speed.